A scientometric analysis of entrepreneurial and the digital economy scholarship: State of the art and an agenda for future research - Natanya Meyer; Foued Ben Said; Nasser Alhamar Alkathiri; Mohammad Soliman (Journal of Innovation and Entrepreneurship, 2023)
Recently, there has been a greater focus on the relationship between entrepreneurship and the digital economy in academia and practice. However, no known work systematically reviews and analyses such a connection, which highlights the need to address this gap by conducting a thorough systematic literature review employing bibliometric and scientometric analyses concerning entrepreneurship and digital economy research. In doing so, analysis of key trends as well as knowledge structure (i.e., intellectual and conceptual) has been employed to analyze, visualize, and map 275 documents gathered from Web of Science (WoS) and Scopus data sets. The number of publications in the current research field has expanded dramatically due to the substantial efforts by major contributors (e.g., researchers, institutions, nations, and academic journals) worldwide. Key research themes, trends, approaches, and outlines were also emphasized by mapping the intellectual, social, and conceptual structures of entrepreneurship and digital economy-related research. The implications, limitations, and agenda for future research were all outlined.
Keywords: 650; Bibliometrics; Digital economy; Entrepreneurship; Research agenda; Scientometric